Polysaccharide Hydrogels Support the Long-Term Viability of Encapsulated Human Mesenchymal Stem Cells and Their Ability to Secrete Immunomodulatory Factors - Fahd Hached; Claire Vinatier; Pierre-Gabriel Pinta; Philippe Hulin; Catherine Le Visage; Pierre Weiss; Jérôme Guicheux; Aurélie Billon-Chabaud; Gaël Grimandi (Hindawi Limited, 2017)
While therapeutically interesting, the injection of MSCs suffers major limitations including cell death upon injection and a massive leakage outside the injection site. We proposed to entrap MSCs within spherical particles derived from alginate, as a control, or from silanized hydroxypropyl methylcellulose (Si-HPMC). We developed water in an oil dispersion method to produce small Si-HPMC particles with an average size of about 68 μm. We evidenced a faster diffusion of fluorescein isothiocyanate-dextran in Si-HPMC particles than in alginate ones. Human adipose-derived MSCs (hASC) were encapsulated either in alginate or in Si-HPMC, and the cellularized particles were cultured for up to 1 month. Both alginate and Si-HPMC particles supported cell survival, and the average number of encapsulated hASC per alginate and Si-HPMC particle (7102 and 5100, resp.) did not significantly change. The stimulation of encapsulated hASC with proinflammatory cytokines resulted in the production of IDO, PGE2, and HGF whose concentration was always higher when cells were encapsulated in Si-HPMC particles than in alginate ones. We have demonstrated that Si-HPMC and alginate particles support hASC viability and the maintenance of their ability to secrete therapeutic factors.